Peran Keluarga dalam Membangun Demokrasi yang Beradab - Nabila Salwa (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
Democracy is not only understood as a political system and state institutional mechanisms, but also as a value and culture of life that must be instilled from an early age. This article aims to examine the role of the family as the primary informal educational institution in developing a civilized democratic character in children. Through a literature review and descriptive-qualitative analysis, this article examines the concept of family-based democratic education, referring to theories of social and moral development and the dynamics of Indonesian democracy over time. The study's findings indicate that families play a strategic role in instilling democratic values ​​such as justice, responsibility, tolerance, deliberation, and respect for differences through daily practices, including open dialogue, parental moral role models, the division of tasks and responsibilities, and children's involvement in family decision-making. Empirical findings from a case study in Yogyakarta confirm that children raised in democratic families have better social, emotional, and political awareness skills. Family-based democratic education has been shown not only to shape children's behavior within the home environment but also to prepare them to become critical, ethical citizens capable of constructive participation in society and the nation. Thus, the family is the primary and irreplaceable foundation for building a civilized and sustainable democracy.